Conservative Treatment in Impending Fracture of Solitary Brown Tumor of Tibia: A Case Report and Review of Literature - Pakmanee, Nithi; Chobpenthai, Thanapon (International Journal of Innovative Research in Medical Science, 2023)
Background: Brown tumors, also known as osteitis fibrosa cystica, are focal benign bone lesions caused by an increased osteoclastic activity because of high levels of parathyroid hormones. The increase of parathyroid hormones can be primary hyperparathyroidism (HPT) and secondary HPT resulting from renal failure and vitamin D deficiency. Case presentation: A 26-year-old Thai female visited the clinic because of right leg pain and swelling for three weeks. Plain radiography revealed a solitary osteolytic lesion with an impending fracture at the anterior cortex of the right proximal tibia. The patient underwent a core needle biopsy. The initial histopathology report depicted a giant cell lesion. In addition, the patient had elevated serum parathyroid hormones. A parathyroid adenoma was discovered on a further investigation with contrast-enhanced computed tomography of the neck. The immunochemistry and molecular study report were consistent with a brown tumor. The patient underwent parathyroidectomy for her adenoma and was on weight-bearing restrictions for her leg. After three months of follow-up, she could bear weight on her right leg without pain, and radiographic evaluation showed restoration of the tibial cortex. Conclusion: Conservative management has a role in managing brown tumors of the lower extremities with impending pathologic fracture. Rapid diagnosis and removing the primary cause of parathyroid adenoma as soon as possible is a crucial part of the treatment.